Biokonversi Limbah Organik Menjadi Magot Sebagai Sumber Protein Pengganti Tepung Ikan - Nefi Andriana Fajri; Ria Harmayani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Bioconversion is one of the ways to treat organic waste (market abundance) which is a problem today, namely by utilizing microorganisms such as Black Soldier Fly (BSF) larvae as biodegradation agents. This study aims to study the life cycle of BSF in market waste media and to determine the potential of BSF larvae to break down market waste. This research was conducted for 8 months starting from the pre-study until the implementation of the study. The observation phases carried out in this study included 1) the life cycle of BSF in the chopped and non-chopped organic market waste media. 2) the potential of BSF larva / maggot in breaking down chopped and not chopped organic market waste. The results showed that the hatching process from eggs to larvae took three to four days. The larval phase which is still yellowish white lasts approximately 12 days, in this phase the larvae will need a lot of food. The prepupa phase occurs from the 19th day and the pupal phase is 100% achieved on the 24-26th day. Maggot has the ability to degrade market waste up to 84 ± 4.90% in market waste that is enumerated and around 69 ± 5.83% breaks down market waste that is not chopped